PENGARUH PENERAPAN INTEGRATED READING AND WRITING TASK DALAM PROBLEM BASED LEARNING (PBL) SEBAGAI STRATEGI UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS DI SMP NEGERI 03 PANA - Gustina Gustina; Yusniar Rasjid; Suryanti Sombo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2022)
This research is an experimental research that aims to determine the effect of implementing integrated reading and writing tasks in problem based learning (PBL) as a strategy to improve scientific literacy skills at SMP Negeri 03 Pana. This research is experimental using a single group pretest – posttest design. The population in this study was a group of class IX students of SMP Negeri 03 Pana while the sample used purposive sampling and the sample in this study were students of class IX SMP Negeri 03 Pana. The data analysis technique used is descriptive analysis and inferential analysis. The results showed that, 1) in the pretest category of students' scientific literacy abilities, namely 22 students or 88% were in the very low category, with an average of 54.4. In the posttest scientific literacy category, 23 students or 92% were in the very good category. The T test shows that the value of Tcount = 13.423 > Ttable = 1.71 can also be seen from the level of significance if it is accepted that H0 = sig> 0.05 (5%) or accepted H1 = sig <0.05 (5%), it is known that the significance value is 0.001. Because the sig value is 0.001 < 0.05. Thus it can be concluded that H1 is accepted, then there is a significant influence. The effect of implementing integrated reading and writing tasks in problem based learning (PBL) as a strategy to improve scientific literacy skills at SMP Negeri 03 Pana